E-Logbook Pengunjung Perpustakaan Berbasis Web Menggunakan Metode Rapid Application Development - I Made Dwi Ardiada; Agus Tommy Prawira Kusuma; Prastyadi Wibawa Rahayu (Elkom : Jurnal Elektronika dan Komputer, 2024)
Every university certainly has a library to provide learning facilities to the academic community. According to Article 55 of the National Education System Law Number 2 of 1989, one of the requirements to have a university is to have a library. The development of libraries today has shifted from systems that initially still used manual systems, to automated systems that can later be developed into online service systems or digital libraries. However, in this case, according to the findings at the time of college accreditation, the recording of library visitors still uses a ledger that is handwritten by visitors. in terms of college accreditation, it is necessary to use a web-based Library Visitor E-Logbook that has a positive and significant impact. In this study, the manufacture of the E-Logbook system uses the Rapid Application Development method and produces system requirements that have 2 access rights, namely Visitors and Library Operators as well as System Design, Database Design in the form of Entity Relationship Diagrams and Web-based system applications. From this research, the Library Visitor E-Logbook system can provide benefits in administrative processes related to recording and monitoring computerized visitor visits and is able to provide convenience in searching data and downloading visitor reports